Active nonlinear partial-state feedback control of contacting force for a pantograph–catenary system. (August 2019) - Zhu, Bing; Ren, Zhiling; Xie, Wenjing; Guo, Fengyi; Xia, Xiaohua
Abstract: In this paper, a nonlinear partial-state feedback control is designed for a 3-DOF pantograph–catenary system by using backstepping approach, such that the contacting force of the closed-loop system is capable of tracking its reference profile. In the control design, the pantograph–catenary model is transformed into a triangular form, facilitating the utilization of backstepping. Derivatives of virtual controls in backstepping are calculated explicitly. A high-order differentiator is designed to estimate the unknown time derivatives of elasticity coefficient; and an observer is proposed to reconstruct the unmeasurable states. It can be proved theoretically that, with the proposed nonlinear partial-state feedback control, the tracking error of the contacting force is ultimately bounded with tunable ultimate bounds. Theoretical results are demonstrated by numerical simulations. Highlights: The backstepping approach is firstly applied to control design for pantograph–catenary system. The closed-loop system is capable of tracking not only constant reference contacting force but also time-varying periodic reference forces. A high-order differentiator is designed to approximate the unknown derivatives of time-varying elasticity coefficient. A simple observer is designed to reconstruct the un-measurable system states.